“We tried to work, but no one saw most of the proposals being carried out”: impacts of the Digital Participatory Budget of Volta Redonda between 2017-2020 - Luciano, Evandro Carlos Silva (2021)
This article aims to analyze the contributions of the Volta Redonda Digital Participatory Budget (OPD-VR) in the period 2017-2020 for the effectiveness of social participation in the municipality of Volta Redonda in its local relations and resolution of public problems. To do so, we start from a theoretical framework about participation, democratic deliberation and impacts of the digital participatory budget. Methodologically, we placed a qualitative research with the support of questionnaires and semi-structured interviews conducted with relevant members who work directly in the OPD-VR. From the Triangulation Technique, we created the categories "Participation", "Representation", "Social Control and Transparency" and "Distribution of Resources" to analyze and justify the analytical potential of digital participatory budgets in their concept, practice, reach, availability and intervention capacity. However, in the case of Volta Redonda, we observe that the mechanisms of digital participation that prioritize individual actions, do not offer spaces for collective deliberation and, in a certain way, diminish the collective importance of participation.